The sanctioning of warfare: Early lessons from the EU's geoeconomic response to Russia's invasion of Ukraine - Kim B. Olsen (Danish Institute for International Studies (DIIS), 2022)
In February 2022 the EU was confronted with the acute security threat, flouting of international law and resultant humanitarian crisis at its borders provoked by Russia's military aggression against Ukraine. The EU launched a massive 'geoeconomic' response in the shape of several packages of economic and financial sanctions. This policy report investigates and compares the early lessons learned in different EU institutions and Member States during the first six months of this 'sanctioning of warfare'. Based on an analysis of the opportunities and challenges at various phases of the 'sanctions policy cycle', the report recommends: i) better scenario planning; ii) stronger building of smaller coalitions among pro-sanction Member States; iii) a more coherent integration of trade, defence, and security experts into EU decision-making processes; iv) a more proactive effort to improve national sanctions laws of Member States to support implementation; v) a more prudent strategic application of sanctions rather than as tit for tat responses to tactical military developments; and vi) clearer communication from policymakers about where sanctions hold the potential to trigger unintended economic and security-related consequences.
Keywords: 300; Europe; Russia; Ukraine; EU; Sanctions; warfare; geoeconomy; European security